PENANGANAN KELUHAN TAMU (HANDLING COMPLAINT) OLEH RECEPTIONIST DI HOTEL GRAND JATRA PEKANBARU - Ulina, Sri; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Grand Jatra Hotel is a 5 star hotel that stands right in the city center of the Pekanbaru Riau area. The Grand Jatra Pekanbaru Hotel is not free from various complaints from guests. Complaints can be categorized into two categories, namely mild complaints and serious complaints. This is specifically handled by the Receptionist. Handling complaints carried out and handled specifically by the receptionist is part of the complaint handling strategy and aims to make complaint handling more focused and able to answer complaints optimally. This research was conducted with the aim of analyzing the strategies used, especially in handling complaints, as well as supporting environmental factors in handling complaints, such as the handling procedures carried out by the Receptionist at the Grand Jatra Hotel Pekanbaru. This research uses qualitative research methods. Data collection was carried out by observing and continuing with interviews and documentation. Keywords: Hotel, Front Office, Receptionist